Importance of intraoperative enteroscopic biopsy in diagnosis of Crohn’s disease: Case Report - Cruzado-Castañeda, Julio C (2025)
Crohn's disease (CD) is a chronic inflammatory bowel disease with no “gold standard” for diagnosis. This report, describing the case of a 31-year-old woman with Turner syndrome and chronic recurrence of bloody diarrhea, emphasizes timely diagnosis by intraoperative enteroscopy. The patient, in addition to diarrheal symptoms, presented abdominal pain and severe anemia, which were initially misdiagnosed as celiac disease and then as intestinal tuberculosis. After multiple tests and treatments, a biopsy by intraoperative enteroscopy identified chronic granulomatous ileitis, confirming the diagnosis of CD. This finding was crucial to adjust treatment and significantly improve symptoms. The case  highlights the importance of accurate diagnostic evaluation in patients with complex comorbidities and the value of intraoperative enteroscopy in diagnosing inflammatory bowel diseases. The main lessons learned are the need for a correct diagnosis to avoid unnecessary treatments and to optimize clinical management, which resulted in a substantial improvement in the patient's quality of life.